Keanekaragaman Dan Kemerataan Serangga Pada Areal Tanaman Kentang (Solanum tuberosum L) Setelah Berbagai Metode Aplikasi Insektisida - Evawani Tomayahu (Agrologia, 2015)
Pest is one of the biological limiting factors that led to low production of potatoes. The use of pesticides is a solution in controlling pests. The objective of this study was to determine the diversity and evenness of insect; and potato yield losses due to insecticide applications methods. The treatment was controlled and intensive insecticide application which were compared with no insecticide application.  The experiment was set up in completely randomized design with five replications. The results showed that the insects are dominated by Empoasca sp, Liriomyza sp and Miridae. The highest insect population was Empoasca sp. i.e 80.83 Empoasca sp. which was found in control treatment. Controlled and intensive  application of insecticides decreased insect  population up to 56.50 and 26.17. Evenness index of insect and economic value of lost results unaffected by differences in pesticide application methods